Effect of inoculation of Burkholderia sp. strain SJ98 on bacterial community dynamics and para-nitrophenol, 3-methyl-4-nitrophenol, and 2-chloro-4-nitrophenol degradation in soil - Jun Min; Bin Wang; Xiaoke Hu (Scientific Reports, 2017)
Abstract para-Nitrophenol (PNP), 3-methyl-4-nitrophenol (3M4NP), and 2-chloro-4-nitrophenol (2C4NP) are highly toxic compounds that have caused serious environmental issues. We inoculated an artificially contaminated soil with Burkholderia sp. strain SJ98, which has the ability to degrade PNP, 3M4NP, and 2C4NP, and quantified bioremediation. There was accelerated degradation of all nitrophenols in inoculated treatments compared to the un-inoculated treatments. The indigenous bacteria were able to degrade PNP, but not 3M4NP or 2C4NP. Real-time PCR targeting the catabolic gene pnpA showed that levels of strain SJ98 remained stable over the incubation period. High-throughput sequencing revealed that both contamination and bioaugmentation influenced the bacterial community structure. Bioaugmentation seemed to protect Kineosporia, Nitrososphaera, and Schlesneria from nitrophenol inhibition, as well as led to a sharp increase in the abundance of Nonomuraea, Kribbella, and Saccharopolyspora. There was a significant increase in the relative abundances of Thermasporomyces, Actinomadura, and Streptomyces in both contaminated and bioaugmented treatments; this indicated that these bacteria are likely directly related to nitrophenol degradation. To our knowledge, this is the first report of the simultaneous removal of PNP, 3M4NP, and 2C4NP using bioaugmentation. This study provides valuable insights into the bioremediation of soils contaminated with nitrophenols.